The effectiveness of McDonald Transvaginal Cerclage in preventing preterm labor - Pribadi, Adhi (Majalah Obstetri & Ginekologi, 2023)
HIGHLIGHTS Cervical cerclage is effective to prevent preterm birth. The use of silk thread (monofilament) or ribbon for suture material is successful in maintaining pregnancy.   ABSTRACT Objective: To determine the success and effectiveness of the use of McDonald's transvaginal cerclage techniques and the thread material used to prevent premature labor in cases of uterine cervical incompetence. Case Report: This was a retrospective study. Data for 13 patients were taken from the medical records of Dr. Hasan Sadikin Hospital, Bandung, Indonesia, and private clinics from the years of 2009 to 2021. The procedure used was a McDonald's cerclage technique with material suture using silk no. 1 and mersilene tape thread. Indications were used based on a previous history of obstetrics preterm, abortion beyond 13 weeks or based on cervical length. The criterion for cerclage success was achieving pregnancy at 36 weeks. Adjuvant therapy using tocolytics was administered intermittently in all patients. The patient was advised to douch the vagina using an antiseptic if there was excessive vaginal discharge. According to the success criteria, 92% of elective McDonald cerclages were able to maintain a pregnancy well up to 36 weeks. A total of 11 elective cases used silk no. 1, while mersilene was used in 1 case. The silk no. 1 thread material was used in the elective cases with 91% success. One case using mersilene tape was able to maintain pregnancy until delivery by cesarean section at 38 weeks of age with bicornuate uterine pathology. One case of emergency cerclage with silk no. 1 failed to maintain pregnancy until 36 weeks. Conclusion: The use of cerclage in conjunction with adjuvant therapy and antiseptic douching efforts has resulted in good success in maintaining pregnancy in cases of cervix incompetence with a history of obstetric preterm and recurrent abortus. When there is no tape-shaped thread material suture, the use of silk thread or other monofilament threads with a larger diameter can be considered.